Plateau-rayleigh instability in low-viscosity ratio stratified liquid-liquid flow - Lugo, Pedro José Miranda (2024)
The stratified liquid-liquid flow is one of the separate flow patterns observed in nature and many industries, including offshore subsea lines and directional wells. That flow is still an open research subject due to its complex interfacial interaction and restricted hydrodynamic stability in specific operational conditions. The literature reports different theories to explain the stratified flow transition. A recent theory suggests that the interfaces cross-section curvature is related to capillary instability, which effect is stronger at high water volumetric fractions. Nevertheless, to the best of the authors knowledge, no experimental study quantifies that effect, and there is no consensus regarding the preponderant instability mechanism for the typical flow conditions observed in practice. In this thesis, the effect of interfacial tension on the transition of horizontal stratified oil-water pipe flow with low Eötvös numbers (Eo = 2.2 and 9.7) is measured using optical techniques in a novel experimental installation designed and built during this research. Unlike most studies, mineral oil and water with a low viscosity ratio of 1.44 are used. Particle image velocimetry (PIV) was used to measure stratified oil-water pipe flow hydrodynamic quantities at the flows longitudinal plane. Geometrical and kinematic properties of the interfacial wave at the flows longitudinal and cross-section planes for stable and unstable flow conditions were determined via planar laser-induced fluorescence (PLIF). The interfacial wave speed was measured by combining planar imaging, shadow sizing techniques, and 1-D cross-correlation function. The axial velocity profiles showed an S-shape profile in the water caused by the drag force exerted by the oil on the water. The radial velocity profiles and velocity fluctuations suggested the presence of secondary flow. The total shear stress showed a change in the slope of the shear stress in the region where the interface was located, which is related to the variation in the intensity of turbulent shear when passing from one phase to another. The interfaces cross-section curvature of stratified pipe flow was measured for the first time. The results indicate that it increases with the increase of the water in-situ volumetric fraction. A linear stability analysis based on the 1-D two-fluid model indicated that capillary instability can be strong enough to lead the transition mechanism from stratified to plug flow at some specific flow conditions.